The Relationship Between Working Posture and Working Duration with Musculoskeletal Disorders (MSDs) Complaints Among Tope Le’Leng Sarong Weavers of the Kajang Ammatoa Tribe in Bulukumba Regency - Massakili, Andi; Mallapiang, Fatmawaty; Ibrahim, Hasbi; Jusriani, Rini (Unihealth Community Research, 2026)
The occupation of weaving Tope Le’leng sarongs among the Kajang Ammatoa tribe carries a high risk of developing Musculoskeletal Disorders (MSDs). This study aims to examine the relationship between occupational factors, specifically working posture and duration of work, and the prevalence of MSDs among Tope Le’leng weavers. This is a quantitative study using a cross-sectional design. The population consisted of all Tope Le’leng sarong weavers in the Kajang Ammatoa tribe, Bulukumba Regency, totaling 42 individuals, with total sampling technique employed. Data were collected using the Nordic Body Map questionnaire to assess MSD complaints and the Rapid Entire Body Assessment (REBA) method to evaluate working posture. Data were analyzed using the Chi-Square test with a significance level of α = 0.05. The results showed a significant relationship between working posture and MSD complaints (p = 0.000), as well as between duration of work and MSD complaints (p = 0.017). Based on these findings, it is recommended that workers take breaks every 1–2 hours during or after weaving for stretching exercises, and use seating cushions and backrests to reduce MSD risks.